Aucubin Protects Chondrocytes Against IL-1β-Induced Apoptosis In Vitro And Inhibits Osteoarthritis In Mice Model - Wang B; Jiang Y; Yao Z; Chen P; Yu B; Wang S (Dove Medical Press, 2019)
Bo-wei Wang,1,* Yi Jiang,1,* Zi-long Yao,1,* Pei-sheng Chen,2 Bin Yu,1 Sheng-nan Wang1 1Department of Orthopaedics and Traumatology, Nanfang Hospital, Southern Medical University, Guangzhou 510515, People’s Republic of China; 2Department of Orthopaedics, Fuzhou Second Hospital Affiliated to Xiamen University, Fuzhou, Fujian 350007, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bin Yu; Sheng-nan WangDepartment of Orthopaedics and Traumatology, Nanfang Hospital, Southern Medical University, No.1838, North Guangzhou Avenue, North, Baiyun District, Guangzhou 510515, Guangdong Province, People’s Republic of ChinaTel +86 20 6164 1741Email yubinortho@sina.com; wsn84@sina.cnObjective: Chondrocyte apoptosis has also been strongly correlated with the severity of cartilage damage and matrix depletion in an osteoarthritis (OA) joint. Therefore, pharmacological inhibitors of apoptosis may provide a novel treatment option for patients with OA. Aucubin, a natural compound isolated from Eucommia ulmoides, has been proved to possess antioxidative and anti-apoptotic properties. However, anti-osteoarthritis effect of aucubin in animal model and anti-apoptotic response of aucubin in OA chondrocytes remain unclear. This study aimed to determine whether aucubin could slow progression of OA in a mouse model and inhibit the IL-1β-induced chondrocyte apoptosis.Methods: OA severity and articular cartilage degradation were evaluated by Safranin-O staining, Hematoxylin-eosin (H&E) staining, and Osteoarthritis Research Society International (OARSI) standards. Chondrocyte viability was observed by Cell Counting Kit-8 (CCK8) and live/dead cells assay; the apoptotic rate of chondrocytes was evaluated by flow cytometry (FCM) with Annexin V-FITC/PI kit. Mediators of apoptosis were tested by Western blot of Bax, caspase-3, caspase-9, and Bcl-2 expression. The intracellular levels of Reactive oxygen species (ROS) were assessed by the probe of 2,7-Dichlorofluorescin diacetate (DCFH-DA).Results: The articular cartilage in the limb with destabilization of the medial meniscus (DMM) exhibited early OA-like manifestations characterized by proteoglycan loss, cartilage fibrillation, and erosion, with lower OARSI score. Oral administration of aucubin remarkably attenuated the loss of proteoglycan and the articular cartilage erosion and decreased the OARSI scores underwent DMM surgery. Aucubin treatment significantly reverses IL-1β-induced cytotoxicity and attenuated the IL-1β-induced chondrocyte apoptosis. In addition, aucubin can significantly inhibit mediators of apoptosis in rat primary chondrocytes. Furthermore, aucubin remarkably attenuated the IL-1β-induced intracellular ROS production.Conclusion: Our findings suggest that aucubin has a protective effect on articular cartilage and slowing progression of OA in a mouse model. This protective effect may result from inhibiting chondrocyte apoptosis and excessive ROS production.Keywords: aucubin, osteoarthritis, apoptosis, ROS, IL-1β